The Effectivity Of Angkle Pump Combination Therapy And Leg Elevation Position Against Lower Limb Oedema Mrs. "M" In The 3rd Trimester - Wilma, Wilma; Intan Fatriana, Yulia; Wahyuni, Sari; Pastuty, Rosyati; Yuka, Aprillia Ayu Shinta (Journal of Maternal and Child Health Sciences (JMCHS), 2024)
Pregnancy causes a lot of changes and adjustments in women that cause discomfort. Discomfort is an unpleasant feeling for the physical or mental condition of pregnant women. Discomfort that appears in pregnant women in the third trimester is an increase in the frequency of urination, constipation, oedema in the lower extremities, insomnia, lower abdominal pain, haemorrhoids, and varicose veins. Oedema in the lower limbs is caused because blood flow from the legs to the heart is inhibited, so nonpharmacological therapy is carried out with angkle pumps and leg elevation positions. This therapy is beneficial for controlling swelling and can help pump blood to the heart through muscle contractions. The purpose of the study was to evaluate how ankle pump therapy and leg elevation position can overcome oedema in the lower limbs in pregnant women in the third trimester. This study is a case study with a comprehensive obstetric care approach to Mrs. M and data collection, observation and management of angkle pump therapy and leg elevation position for 1 (one) week routinely 2-3 times a day with a duration of 5-10 minutes. The results obtained from the discomfort care intervention in the third trimester that the oedema in the lower limbs has been reduced so that it feels comfortable